ANALISIS PENGARUH HARGA, PROMOSI, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN Studi Kasus Pada Pengguna Jasa Penerbangan PT. Garuda Indonesia di Semarang - Ghufran, Abdurrahman; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to determine whether the price, promotion, service quality, and brand image influence on consumers purchase decisions in using Garuda Indonesia flight services. This research also aims to analyze the most dominant factors impact to purchasing decisions on Garuda Indonesia flight servicesThe population used in this research is the consumer who ever or often purchase who ever or often use Garuda Indonesia flight services who domiciled or the cirizens of Semarang City. Samples in this study were 100 respondents and technique used are purposive sampling technique. Data analysis using SPSS (Statistical Package for Social Science).Based on results of the research show that the price, promotion, service quality, and brand image have an influence on consumers purchase decisions in using Garuda Indonesia flight services.